Bio-mechanical Properties of Novel Bi-layer Collagen-Elastin Scaffolds for Heart Valve Tissue Engineering - Chen, Q; Bruyneel, A; Carr, C; Czernuszka, J (2013)
Collagen and elastin are two major components of the extracellular matrix of heart valves. This work examines bi-layer scaffolds made of collagen and elastin for potential use in the tissue engineering of heart valves, by investigating the effects of the layered structure on the mechanical and biological properties. The scaffolds showed anisotropic bending moduli depending on the loading directions (lower when with curvature than against curvature), which mimicked the characteristic behaviour of the native heart valves. The interaction of cardiosphere-drived cells with the scaffolds was characterized by scanning electron microscopy and multiphoton microscopy, and an asymmetrical cell distribution was observed. The bi-layer scaffolds have represented a forwarding step to the tri-layer scaffolds that more closely resemble the native heart valves. © 2013 The Authors.